Efficiency analysis of docetaxel in combination with doxorubicin in first-line chemotherapy in patients with advanced breast cancer in the Wielkopolska Cancer Center - Załuski, Jerzy; Szoszkiewicz, Renata (Contemporary Oncology/Współczesna Onkologia, 2003)
Breast cancer belongs to the most frequent neoplasms in Poland. Chemotherapy is the treatment of choice for advanced localy breast cancer and metastatic breast cancer. The most promising new group of cytotoxic chemotherapeutic agents is taxans. Two types of taxans: paclitaxel (Taxol) and docetaxel (Taxoter) used with anthracycline-containing combinations were often compared with the standard treatment. The results of some phase II and III studies have shown high response rates (80%) when the standard chemotherapy have shown relatively lower response rates (60%). Between August and December 2002 in the Wielkopolska Cancer Center, a group of 17 female patients with advanced breast cancer were treated. The patients’ age was between 36 to 62 and the stage of disease was between IIA and IIIA (IIA – 2 patients, IIB – 5, IIIA – 10). Each patient revealed complete or partial response. The overall response rate of tumor reduction by 72.3% was observed. The complete histopathological regression was recorded in the case of two patients. This therapy was well tolerated and most of the toxicities were generally rare and mild. Although alopecia was revealed by every patient, swelling was found by two persons only, vomiting by seven and nausea by eight. The treatment appeared very effective. Patients were able to undergo successfully further therapy, such as surgery. Phase II and III study proved that Taxanes as targeted therapies can play an important role in the treatment of women with advanced breast cancer.